PENGARUH CLASSDOJO APPLICATION TERHADAP SELF-REGULATED LEARNING DAN KETERLIBATAN ORANG TUA DI SEKOLAH DASAR - Siti Nur Aisyah; Rohmat Widiyanto (Al-Mudarris, 2025)
This study aims to find out the impact of the use of the ClassDojo application on Self-Regulated learning students and the involvement of parents in SD Kharisma Nations. This study is a kunatitative study with regression mode. The sample consisted of 89 students in classes IV–VI and 75 elders. Data is collected through lifting and documentation, as well as analyzed using descriptive statistics, prerequisite tests (normality and linearity), simple regression tests, determinant coefficients, and t-tests. The results showed that the Classdojo application had a positive and significant influence on self-regulated learning of 42.4% (sig. 0,00 dann t. count 6,131). The Classdojo application also has a positive and significant influence on parental involvement (26%). (sig. 0,00 dan t. hitung 3,891). This result depends on the use of Classdojo features such as classroom, class story and portfolios, and messages. a) Classroom features support effective classroom management and positive interaction, which can enhance student motivation and behavior. b) Portfolios enable students to reflect and track their own development, supporting metacognitive aspects. c) Class Story facilitates communication between school and home, encouraging further involvement and motivation from students and their parents. d) Messages facilitate direct communication between parents and teachers. Thus, it can be concluded that the use of ClassDojo can improve the self-regulated learning of students and the involvement of parents in SD Kharisma Nasa. It is recommended that this application be optimized for use by teachers, students, and parents.